Population pharmacokinetic model of isoniazid in patients with tuberculosis in Tunisia. (March 2021) - Fredj, N. Ben; Romdhane, H. Ben; Woillard, J.B.; Chickaid, M.; Fadhel, N. Ben; Chadly, Z.; Chaabane, A.; Boughattas, N.; Aouam, K.
Highlights: To the authors' knowledge, this paper reports the first pharmacokinetic model for isoniazid (INH) for use in North African patients with tuberculosis. Only acetylator status was found to affect the pharmacokinetic parameters in this population. This model allows individualized INH doses to be established based on acetylator status. Initial doses of at least 225 mg/24 h and at least 450 mg/24 h allow attainment of a therapeutic concentration in >80% of patients in the slow acetylator group and rapid/intermediate acetylator group, respectively. Graphical abstract: Abstract: Aims: To develop a pharmacokinetic model of isoniazid (INH) concentration taking into account demographic factors and genetic variables [N-acetyltransferase 2 (NAT2) genotype], and to propose an initial INH dosage that could maximize the probability of achieving the desired INH concentration. Methods: A retrospective analysis was undertaken of INH concentration data collected from patients with tuberculosis in Tunisia. Results: In total, 118 patients were included in this study. The one-compartment model [volume of distribution (V), elimination rate (Ke)] was found to have good predictive performance. Multi-variate analysis showed that NAT2 affected both V and Ke significantly, but age, gender and weight did not. Internal validation of the final model showed correlation of 0.95 between individual predicted INH concentration 3 h after drug intake (C3) and observed C3. External validation showed that percentage mean absolute prediction error and percentage root mean squared error were 9.11% (range 0.62–35.8%) and 11.6%, respectively. Monte-Carlo simulation showed that doses of at least 225 mg/24 h and at least 450 mg/24 h attained a therapeutic concentration in >80% of patients in the NAT2 slow acetylator group and the NAT2 rapid/intermediate acetylator group, respectively. Conclusion: The pharmacokinetic model allowed optimization of individual dosing regimens of INH in patients with tuberculosis in Tunisia. This tool may facilitate improved efficacy of INH and prevent its toxicity in this population.